Influence of Rice Husk Ash on the Physical and Mechanical Properties of Concrete (Aporte Santiaguino, 2024)
The objective was to optimize the amount of cement in a concrete mix. The type of research was applied with experimental design. Dosages of 2, 4 and 6% were proposed. The specific characteristics of the concrete evaluated were the compressive strength, amount of voids and slump. The results showed that the amount of cement was optimized in 9.52k, 28.17, 55.02 kg/m3 and the design strength was met, of 310.19, 301.83 and 283.05 kg/cm2 for dosages of 2, 4 and 6%, respectively. The results of the concrete evaluation, specifically in the air content, indicate that the ash generates greater air voids in the concrete, with a percentage of 2.7, 3.7 and 4.7%. On the other hand, the slump evaluated decreased from 4” to 3.9”, 3.8” and 3.4” for the dosages worked. It is concluded that rice husk ash, in the dosages, fulfilled the goal of optimizing the amount of cement in the concrete design so that it can be used as an air-entraining admixture to reduce slump.
Keywords: Optimization; Cement; Strength; Concrete